Prevalence and significance of sleep disordered breathing in adolescent athletes - Iso, Yoshitaka (ERJ Open Res, 2019)
Sleep disordered breathing (SDB) was more prevalent in adolescent athletes than expected, and several potential warning signs related to autonomic nerve activity appeared in SDB athletes. SDB screening may prevent associated downstream risks in the future. http://ow.ly/GQqK30nGm8r